"Those Who Cannot See the Whole Are Offended by the Apparent Deformity of a Part": Disability in Augustine's City of God. Issue 3 (6th July 2022) - Massmann, Alexander
ABSTRACT: In De ciuitate Dei ( ciu .), Augustine famously calls people with disabilities created on purpose by an absolutely competent God (16.8). On the whole, however, Augustine's views on disabilities in ciu . are often misunderstood. The statement about the creation of people with disabilities is part of a discussion of the theodicy question that implies that the goodness of people with disabilities is not open to experience and must be accepted on faith. This negative background assumption results from Augustine's view that dignity emerges from the embodied beauty, rationality, and utility of the ensouled body (22). Augustine gives several examples of how disabilities reduce dignity along with these dimensions, as "deformity defeats beauty" (19.4). In eternal salvation, however, disabilities will be removed (22). Martyrs will perhaps retain scars in heaven, but these particular scars will be of such a kind that there is "not deformitas in them, but dignitas " (22.19). If in the resurrection for eternal life God removes congenital disabilities that God created so competently, what is their purpose in the first place? Augustine regards disabilities as temporal embodied warnings of eternal corporeal punishment (21.8). As a concluding perspective, the alternative view of disabilities by the Apostle Paul will be considered.